Nitrogen-doped carbon dot anchored 1-D WO3 for enhanced solar water splitting: A nano surface imaging evidence of charge separation and accumulation - Sial, Qadeer Akbar; Singh, Ranveer; Duy, Le Thai; Iqbal, Shahid; Yoo, Il Han; Kalanur, Shankara S.; Seo, Hyungtak (International Journal of Hydrogen Energy, 2021)
Combining WO3 with suitable materials to form heterojunction is essential to overcome the limitations of WO3 to enhance its photoelectrochemical (PEC) water splitting activity. Moreover, a clear understanding of photo-response and charge behavior of materials could lead to the rational design of efficient photoelectrodes. Given this, an efficient strategy is applied to fabricate WO3 heterojunction with nitrogen-doped carbon dots (NCDs) and in-depth characterization to investigate the surface charge dynamics using nano imaging in a relation to the enhanced PEC water splitting activity. The optimized NCDs loading to the WO3 NRs exhibited the enhanced photocurrent density of 1.54 mA cm−2 at 1.23V vs RHE under AM 1.5 G illumination, highest IPCE of ~82 % (at 308.32 nm). The Kelvin probe force microscopy and electrostatic force microscopy reveal that after loading NCDs to the WO3, a relatively smooth charge transport has been observed, which improves the PEC. Furthermore, this work demonstrates the effect of photogenerated charges caused by the NCDs that assist in enhancing the increased photocurrent, hydrogen production efficiency, and stability of the PEC water splitting system. Significantly, the nano imaging characterization utilized in this work could be extended to various photoanodes to study the surface charge dynamics.
Keywords: Band edge position; Carbon dots; Charge dynamics; Nano-imaging; Nanosurfaces; Nitrogen-doped carbon dot; Nitrogen-doped carbons; Photoelectrochemical water splitting; Solar water splitting; Surface imaging; Band edge positions; Nitrogen-doped carbon dots; Photoelectrochemical water splitting; Surface imaging; WO3